2014
DOI: 10.1016/j.pmrj.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Metallosis from Metal‐on‐Polyethylene Total Hips: An Emerging Problem

Abstract: This report describes 2 cases of metallosis from metal-on-polyethylene total hip replacements. Case 1 involved a Stryker rejuvenate implant, which has since been recalled. This patient had minimal symptoms, an elevated cobalt level, and loosening. The patient in case 2 had a Dupuys Pinnacle system, with symptoms of weakness, rash, and hip pain. Abnormal laboratory values include elevated sedimentation rate, C-reactive protein, creatinine, cobalt, and decreased hematocrit. Magnetic resonance imaging revealed sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Interest into their degradation mechanisms and biomechanics has been renewed due to the public withdrawal and recall of some products [11]. A number of recent publications have detailed the clinical presentation at revision, surface topography and regions in which degradation are commonly found [12][13][14][15]. All studies are consistent, reporting that…”
Section: Introductionmentioning
confidence: 99%
“…Interest into their degradation mechanisms and biomechanics has been renewed due to the public withdrawal and recall of some products [11]. A number of recent publications have detailed the clinical presentation at revision, surface topography and regions in which degradation are commonly found [12][13][14][15]. All studies are consistent, reporting that…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported non-MoM THAs, such as metal-onpolyethylene (MoP), to be presenting adverse tissue responses similar to the MoM THAs. An adverse response to MoP implants, such as the formation of pseudotumours, may still be linked to the release of cobalt ions from the metal head [33][34][35], albeit at a lower level. This suggests that any wear/corrosion debris containing cobalt (nano) particulates or ions, may have a detrimental influence on the hip tissue microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Metallosis and pseudotumour formation in human patients with joint arthroplasty is well described in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The generation of particulate wear debris derived from the components of joint prosthesis was initially a complication recognized to occur with implants having metal-on-metal articulation.…”
Section: Discussionmentioning
confidence: 99%
“…Metallosis is a well-described condition in the human medical literature that occurs in association with the use of metal-on-metal and metal-on-polyethylene (MoP) orthopaedic joint implants. The condition has been described after total hip replacement (THR), total shoulder replacement, and total knee replacement as well as in cases of uni-compartmental knee arthroplasties (1)(2)(3)(4)(5)(6). Metallosis refers to the chronic inflammatory response resulting from infiltration of the peri-prosthetic soft tissue and bone by biologically reactive metallic wear debris.…”
Section: Introductionmentioning
confidence: 99%